Kitsch and Morality - Aziz Alfailakawi (ESPES)
Throughout the realm of aesthetics there is the general sentiment that kitsch is inherently immoral. Although kitsch itself is a relatively ambiguous term, objects falling into this category are charged with a negative ethical stigma due to their being sentimental and manipulative. In this paper, I articulate the shakiness of the claim that kitsch is immoral by first comparing three accounts of kitsch to demonstrate how the term “kitsch” can be applied (or denied) to various aesthetic objects. I then argue that the charges of sentimentality and manipulation create further ambiguities regarding kitsch. I conclude that although certain objects can be kitsch, to categorically denounce kitsch on an ethical basis is too strong a claim.